A Simple Screening Method for Individuals at Risk of Developing Type 1 Diabetes: Measurement of Islet Cell Autoantibodies (GADA, IA-2A, and IAA) on Dried Capillary Blood Spots Collected on Filter Paper - Siraj, E. S.; Rogers, D. G.; Gupta, M. K.; Reddy, S.S. K. (Hormone and Metabolic Research, 2012)
There is limited information regarding the use of dried capillary blood spots collected on a filter paper (FP) to test for islet cell antibodies. The aim of this study was to validate the use of dried capillary blood spots collected on a FP for the analysis of islet cell antibodies. FP eluates were tested using both single and combined assay for antibodies to glutamic acid decarboxylase (GADA) and/or to the protein tyrosine phosphatase like IA-2 (IA-2A), and a single assay for antibodies to insulin (IAA). The results were compared with those of serum assays. Ninety-one subjects were studied. Forty had Type 1 diabetes mellitus (T1DM) and 51 were first-degree relatives (FDR) of patients with T1DM. The GADA and IA-2A were measured by radio-binding assays, which utilize 35S-labeled GAD65 and IA-2. IAA was measured by a microtiter plate assay using 125I-labeled insulin. Twenty-six of those with T1DM (65%) and 5 of the FDRs (10%) had at least 1 positive test on the single serum assays. The FP combi-assay for GADA and IA-2A had 97.8% concordance rate when compared with serum single assays for GADA and IA-2A. The concordance rate for individual assays were 96.7% for GADA, and 100% for both IA-2A and IAA There was significant correlation of the antibody levels between FP and serum specimen for all 3 antibodies. We conclude that antibody screening performed using dried capillary blood spots collected on a FP correlates well with serum assays, and provides an easy alternative for population screening.
Keywords: type 1 diabetes mellitus; autoimmunity; screening; prediction